Inside African Private Higher Education: Contradictions and Challenges - Morley, Louise (International Higher Education, 2014)
This article discusses the findings that relate to quality and standards in two private universities from a recent research study on widening participation in higher education in Ghana and Tanzania. It interrogates how students experience assessment, facilities, pedagogy and resources and whether the private universities attach value to the quality of student experiences.